Brexit: Could France Follow the Lead? - R. I. Blagoveshchenskii (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Politicians and scholars generally agree that the UK’s withdrawal from the European Union (‘Brexit’) is a unique phenomenon caused by a specific combination of domestic political, economic and social factors, which cannot recur in any other EU country, at least in the foreseeable future. The paper challenges these assumptions by advancing two hypotheses. Firstly, the author argues that Eurosceptic sentiments are almost as common in France as they once were in the UK, and, secondly, that it exactly in France where the next referendum on membership in the European Union could take place. In order to support these hypotheses, in the first section the author examines the main causes and the background of Brexit. The author identifies four key factors: 1) growing discontent of the local population with social and economic issues, which the supporters of Brexit ascribed to the inflow of cheap labor from Eastern Europe; 2) concerns about the possibility of losing national sovereignty as the power of EU supranational bodies increases; 3) support for Brexit on the part of certain political elites; 4) post-imperial syndrome. The second section shows that similar objective trends and public sentiments are developing in France, although can take different forms. As in the UK, certain segments of the French population show growing concern about the prospect of losing national sovereignty given the country’s declining influence within the EU, and call to curb immigration (mainly from North Africa). Additionally, what makes France’s case really unique is that both rightand left-wing eurosceptics are consistently strengthening their influence in the Fifth Republic. All this imposes greater demands on the current president-euroenthusiast E. Macron: his failure may provoke a systemic crisis within the EU, which it might not endure.